Analisis Literatur Administrasi Supervisi Pendidikan dalam Meningkatkan Kinerja Guru di Sekolah Islam - Ristiani Arnila; Sapuadi (PT. Hasba Edukasi Mandiri, 2025)
This researchaims to examine in depth the concept and implementation of educational supervisionadministration in the context of Islamic schools through a literature study approach. Systematic and structured educational supervisionhas been proven to improve teacher performance and learning quality. Moreover, the integration of Islamic values in supervisory practices is a key factor in creatinga moral and religious academic culture. This study relies onrelevant secondary sources, such as scientific journals, academic books, andconference articles, to analyze effective supervision models andtheir contribution to teacher professionalism in Islamic schools. The results of the analysis show that principals or supervisors who act assupervisory leaders have a major influence in guiding teachers constructively andsustainably. These findings provide a theoretical and practical basis for thedevelopment of Islamic education supervision policies that are focused, planned, androoted in Islamic values.